“Their Color is a Diabolic Die,” Colonialism and the State of Environmental Justice in Africa - Arowolo, Ayoyemi Lawal; Lalude, Olalekan Moyosore (Society & Sustainability, 2022)
Environmental justice is crucial to the discourse on the African environment since Africa bears a significant share of the world’s resources, and conversely, it is home to a large number of globally disadvantaged people, whose access to the wealth of their native lands is beyond their reach. Therefore, it is necessary to examine how colonialism and the structures it has laid down in Africa are impeding environmental justice. Content analysis was used in the data collection. In this article, drawing from the slum arrangements in the cities of four African countries colonized by the British and French as case studies, it was revealed how colonialism has caused the degeneration of the African environment. Furthermore, colonialism created a class system that has fed social and economic inequality and has resulted in an intra-racial system of oppression that has made Africa’s poorest neighborhoods more vulnerable.